How do you solve this equation using substitution: 3x-y=14 2x+y=16
the Y values cancel each other out so it becomes 5x=30, 5 divides into 30 6 times.
using substitution, not elimination
Or solve one of the equations for y, then plug it in to the other equation.
Like y=-2x+16, then plug this into the other one: 3x-(-2x=16)=14 Solve for x, then place this the number back into the first equation.
So 3x+2x-16=14 5x-16=14 x=6
So x=6 and now place that back into the other equation: 2(6)+y=16 12+y=16 y=4